Analytical modeling of threshold voltage for nanoscale Symmetric Double Gate (SDG) MOSFET with ultra thin body (UTB) - Vishvakarma S.K.; Raj B.; Singh R.; Panda C.R.; Saxena A.K.; Dasgupta S. (My University, 2025)
In this paper an analytical modeling of threshold voltage is carried out for lightly doped Nanoscale Mid Gap Symmetrical Double Gate (SDG) MOSFET based on solution of two dimensional Poisson's Equation in the active area of the device under suitable boundary conditions. The variation of threshold voltage with doping density, channel length, channel thickness and oxide thickness is carried out in this paper. For the purpose of verification, the results have been compared with those obtained from ATLAS. © 2007 IEEE.